Pemberdayaan Masyarakat dalam Pelestarian Warisan Budaya melalui Festival Pituturan Kendal di Kecamatan Pageruyung - Mirza, M Yusril (Jurnal Pemberdayaan Masyarakat, 2025)
Festivals with various activities held can be an effort to preserve cultural heritage. Because festivals are celebratory events that can attract the enthusiasm of many people and can be packaged according to their objectives. This is realized through the Kendal Pituturan Festival which is designed in the form of a regional cultural festival held by surrounding locations in seven sub-districts in Kendal Regency, one of which is in Pageruyung District. Activities carried out with a collaborative approach and inviting various partners from the community around this location can be an event for community empowerment that provides material and non-material benefits, ranging from improving the economy, social, skills, and experience. This was then proven from the entire process of the implementation stage of the activity, starting from coordination and pre-activity preparation, activity realization, to activity evaluation. Overall, the Kendal Pituturan Festival in Pageruyung District was carried out smoothly and without any obstacles. Various positive responses indicate that the festival can be a useful activity and is expected to be a model for the implementation of further activities.